2020
DOI: 10.1126/sciadv.abc3175
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized extracellular matrix scaffolds identify full-length collagen VI as a driver of breast cancer cell invasion in obesity and metastasis

Abstract: The extracellular matrix (ECM), a major component of the tumor microenvironment, promotes local invasion to drive metastasis. Here, we describe a method to study whole-tissue ECM effects from disease states associated with metastasis on tumor cell phenotypes and identify the individual ECM proteins and signaling pathways that are driving these effects. We show that decellularized ECM from tumor-bearing and obese mammary glands drives TNBC cell invasion. Proteomics of the ECM from the obese mammary gland led us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 39 publications
5
136
1
1
Order By: Relevance
“…Currently, 3D systems with tunable ECM stiffness, bioprinted 3D cell culture systems incorporating TME, systems based on 3D culture of patient's tumor tissue, and systems utilizing decellularized ECM from the patient's tumor have been established (82)(83)(84)(85). Such systems have a clear potential for use in translational oncology.…”
Section: D Cell Culture Models Incorporating Tme As a Testing Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, 3D systems with tunable ECM stiffness, bioprinted 3D cell culture systems incorporating TME, systems based on 3D culture of patient's tumor tissue, and systems utilizing decellularized ECM from the patient's tumor have been established (82)(83)(84)(85). Such systems have a clear potential for use in translational oncology.…”
Section: D Cell Culture Models Incorporating Tme As a Testing Systemmentioning
confidence: 99%
“…Three-dimensional cell culture systems also have proven to be a "biomarkers goldmine"-a valuable tool for biomarker identification (88). For example, using 3D culture model with decellularized ECM scaffolds (dECM) allowed to identify fulllength Collagen VI as a driver of breast cancer cell invasion in obesity and metastasis (89). In colorectal cancer, the patterns of expression of miRNA dependent on 3D microenvironment have been characterized, and one of them (miR-142-5p) was identified as a theranostic biomarker (90).…”
Section: D Cell Culture Models Incorporating Tme As a Testing Systemmentioning
confidence: 99%
“…As a regulator of PI3K signaling, the expression IGFBP2 is strongly correlated with grade of malignancy in many tumors and especially in breast cancer [59] . Collagen VI has been recently identified as driver of invasion and metastasis of breast cancer and high protein levels of Collagen VI have been found by bulk tumor proteomic analysis of more than 500 human cancers 60 , 61 , 62 . Strongly elevated levels of both POSTN and FN1 are well documented in a wide variety of tumors, including breast cancer, and have been shown to promote tumor invasion and metastasis through manifold effects on different cancer hallmarks (reviewed in [ 63 , 64 ]).…”
Section: Discussionmentioning
confidence: 99%
“…P4HA1 has recently been found to overexpress in gliomas and HNSCC; its expression associated with tumor microvessel density ( Li et al, 2019 ). Recent studies have shown that increased production of collagen is linked to BC progression, adhesion, and invasion ( Xiong et al, 2018 ; Wishart et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%